Jøderne i diasporaen i romersk tid - Bilde, Per (Religionsvidenskabeligt tidsskrift, 1993)
In earlier research the situation of the Jews in the Western diaspora in the Roman period was often described as being essentially different from that of the Jews in Palestine: The diaspora-Jews were genrally regarded as more "hellenized" and less "militant". The aim of this article is to question such a traditional interpretation. This program is carried out in the following way: We begin and end by presenting and discussing the general situation of both parts of the Jewish world. However, the substance of the argument consists of analyzing the situation of the Jews in the diaspora in three specific cities, and by discussing the cases of the three personalities of Philo, Josephus and Paul. This analysis is followed by a brief general discussion of the relations between the Jews - both in the diaspora and in Palestine - and the Roman government. In addition, in order to obtain an adequate perspective, the Jewish diaspora is compared with that of other ethnic groups such as the Greeks, the Syrians and the Egyptians at the same time. On this basis, finally, the conclusions are drawn with the result that, although the situation was generally the same for the Jews in the Western diaspora and the Jews in Palestine, there still exist some important differences which we have to keep in mind when discussing these two groups.